دور الذكاء الاصطناعي في الحد من الفجوة التعليمية بمعاهد علوم وتقنيات النشاطات البدنية والرياضية - دحية مراد (My University, 2025)
The study aimed to highlight the role of artificial intelligence in bridging the educational gap at Institutes of Science and Technology of Physical and Sports Activities. It was a field study conducted with professors from these institutes in eastern Algeria. The study was applied representative sample through a comprehensive survey consisting of 224 professors from Institutes of Science and Technology of Physical and Sports Activitiesat universities in eastern Algeria. A descriptive analytical approach was utilized, relying on a questionnaire as a study tool. The results of the study showed several key findings: artificial intelligence does play a role in reducing the educational gap in Institutes of Science and Technology of Physical and Sports Activities; digital systems, digital content, and smart education contribute to closing the educational gap, according to the professors' perspectives. There were no statistically significant differences in the professors' views on artificial intelligence and the educational gap based on gender and professional experience. However, there were statistically significant differences related to age and academic rank.
L'étude visait à mettre en évidence le rôle de l'intelligence artificielle dans le comblement de l'écart éducatif au sein des Instituts des Sciences et Techniques des Activités Physiques et Sportives. Il s'agissait d'une étude de terrain menée auprès de professeurs de ces instituts dans l'est de l'Algérie. L'étude a été appliquée à un échantillonreprésentatif, constitué par un recensement exhaustif composé de 224 professeurs d'instituts des Sciences et Techniques des Activités Physiques et Sportivesdans les universités de l'est de l'Algérie. Une approche analytique descriptive a été utilisée, s'appuyant sur un questionnaire comme outil d'étude. Les résultats de l'étude ont révélé plusieurs conclusions clés: l'intelligence artificielle joue effectivement un rôle dans la réduction de l'écart éducatif dans les Instituts des Sciences et Techniques des Activités Physiques et Sportives; les systèmes numériques, le contenu numérique et l'éducation intelligente contribuent à combler cet écart éducatif, selon les perspectives des professeurs. Il n'y avait pas de différences statistiquement significatives dans les opinions des professeurs sur l'intelligence artificielle et l'écart éducatif en fonction du genre et de l'expérience professionnelle. Cependant, il existait des différences statistiquement significatives liées à l'âge et au rang académique.
Keywords: artificial intelligence; educational gap; digital systems; digital content; smart education; institutes of physical activity and sports sciences.; الذكاء الاصطناعي؛ الفجوة التعليمية؛ الأنظمة الرقمية؛ المحتوى الرقمي؛التعليم الذكي؛ معاهد علوم وتقنيات النشاطات البدنية والرياضية; intelligence artificielle; écart éducatif; systèmes numériques; contenu numérique; éducation intelligente; instituts des sciences de l'activité physique et du sport.